Study of Factors Influencing the Implementation Building Information Modelling (BIM) in Construction Project - Arifin, Ari Syaiful Rahman; Zakiyyah, Ulfah; Giatman, M.; Ashar, Faisal (Universitas Negeri Padang, 2023)
Building Information Modelling (BIM) has become a major trend in the global construction industry. In Indonesia, socialization on BIM has been carried out, but its implementation has not been fully implemented. Therefore, it is necessary to study the factors that influence the application of BIM in construction projects. The purpose of this research is to identify the factors that influence the implementation of BIM in construction projects in the city of Padang, Indonesia. This research was conducted on construction service providers and used a descriptive research design with a quantitative approach. The research sample consisted of 28 companies with a total of 84 respondents using a purposive sampling technique. Primary data collection methods include questionnaires and interviews. The results of this study are Barrier factors and strategic factors in BIM implementation. The barrier factors in BIM implementation on construction projects according to ranking, namely (1) limited Human Resources (22%), (2) Lack of Standards and Guidelines (21%), (3) Lack of Support from Stakeholders (20%), (4) Cost (19%) and (5) Limited Infrastructure and Technology (18%). The strategic factors in BIM implementation on construction projects, according to ranking, are (1) Technical and Technology (21%), (2) Human Resources (20%), (3) Management (20%), (4) Stakeholders and Regulations (20%) and (5) Organization (19%). This study highlights the dominant factors influencing BIM implementation in the construction industry and provides valuable insights for stakeholders to enhance and accelerate BIM implementation in the region.